2016
DOI: 10.2136/sssaj2015.07.0280
|View full text |Cite
|
Sign up to set email alerts
|

Hog‐Manure‐Recovered Struvite: Effects on Canola and Wheat Biomass Yield and Phosphorus Use Efficiencies

Abstract: Recovery of manure P as magnesium ammonium phosphate hexahydrate (MgNH 4 PO 4 •6H 2 O), commonly known as struvite, can mitigate the risk of P contamination of surface water bodies from hog operations. The slow release of P from struvite may help improve crop P use efficiency. This greenhouse bioassay evaluated the agronomic effectiveness of liquid hog manure recovered struvite. Struvite, monoammonium phosphate (MAP), and polymercoated MAP (CMAP) were evaluated for canola (Brassica napus L.) grown in rotation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 33 publications
5
24
0
Order By: Relevance
“…Some authors reported different rates of P released from struvite due to edaphic properties and crop characteristics, Table 3. Olsen P (mg kg -1 soil) of all treatments during the incubation time such as root exudates (González-Ponce et al, 2009;Ackerman et al, 2013;Katanda et al, 2016;Talboys et al, 2016). Ackerman et al (2013) found lower production of biomass per unit of P from struvite, compared with MAP and PCMAP, due to a lower initial solubility of struvite in the alkaline soil used.…”
Section: Resultsmentioning
confidence: 99%
“…Some authors reported different rates of P released from struvite due to edaphic properties and crop characteristics, Table 3. Olsen P (mg kg -1 soil) of all treatments during the incubation time such as root exudates (González-Ponce et al, 2009;Ackerman et al, 2013;Katanda et al, 2016;Talboys et al, 2016). Ackerman et al (2013) found lower production of biomass per unit of P from struvite, compared with MAP and PCMAP, due to a lower initial solubility of struvite in the alkaline soil used.…”
Section: Resultsmentioning
confidence: 99%
“…Further, Weissengruber et al (2018) concluded that potentially toxic element and persistent organic pollutant accumulations would be low to negligible even after 200 yr of struvite application (at 11 kg P ha −1 yr −1 ). In addition to recovery from municipal wastewater, recovery and use (as a fertilizer) of struvite from human urine, livestock urine and manure, and food processing wastes have received considerable attention (Antonini et al, 2012; Achat et al, 2014; Uysal et al, 2014; Katanda et al, 2016; Brown et al, 2018; Katanda et al, 2019; Muhmood et al, 2019). Struvite P recovery potential from municipal and agricultural wastewater ranges from 10 to 99%, depending in part on the process used and the source and P concentration of the waste product (Jordaan et al, 2010; Egle et al, 2016; Peng et al, 2018; Muhmood et al, 2019).…”
Section: Recycling and Recovering Phosphorus From Waste Streams Back mentioning
confidence: 99%
“…Struvite is generally considered a slow‐release fertilizer due to its low solubility in water and relatively slow dissolution in soil (Bridger et al, 1962; Cabeza et al, 2011; Achat et al, 2014; Talboys et al, 2016). The value of struvite as a crop fertilizer has been investigated in many recent studies (Gell et al, 2011; Katanda et al, 2016; Degryse et al, 2017; Katanda et al, 2019) and summarized in several thorough reviews (Liu et al, 2013; Rahman et al, 2014; Kataki et al, 2016; Ahmed et al, 2018; Möller et al, 2018; Peng et al, 2018) and one meta‐analysis (Huygens and Saveyn, 2018). …”
Section: Recycling and Recovering Phosphorus From Waste Streams Back mentioning
confidence: 99%
See 1 more Smart Citation
“…Struvite is not nearly as soluble as MAP (Degryse et al, 2017), so the risk of salt toxicity to seedlings is much less for struvite (Katanda et al, 2019). Growth chamber experiments in Manitoba demonstrated that the P nutritional value of struvite derived from liquid manure was variable, being similar, slightly less, or slightly greater than that for MAP, depending on the soil and crop (Ackerman et al, 2013; Katanda et al, 2016). …”
Section: The 4r Package Of Management Practicesmentioning
confidence: 99%